(untitled) (Philological Studies, 2022)
The article deals with the ruble (рубль) and kopeck (копейка) monetary units. We researched the values expressed in Russian proverbs with the lexemes of ruble and kopeck. Furthermore, we explored the cultural specificities of Russian proverbs, discussing the historical use of the mentioned monetary units in their political and cultural environment. Due to the extensiveness of the topic, this article does not contain all proverbs from the collected corpus. In this paper, we will single out only the syntagms with the elements ruble and kopeck, numerical relations that emerge from syntagms with numbers, and proverbs containing other monetary units. The aim of this paper is to determine the dominant values expressed in proverbs as a reflection of the value system of the community.